Yolk–shell nanostructures: synthesis, photocatalysis and interfacial charge dynamics. Issue 20 (29th March 2021) - Chen, Yi-An; Wang, Yu-Ting; Moon, Hyun Sik; Yong, Kijung; Hsu, Yung-Jung
Abstract : This review gives a comprehensive retrospection on the preparation and photocatalytic applications of yolk–shell nanostructures with additional focus on the realization of interfacial charge dynamics. Abstract : Solar energy has long been regarded as a promising alternative and sustainable energy source. In this regard, photocatalysts emerge as a versatile paradigm that can practically transform solar energy into chemical energy. At present, unsatisfactory conversion efficiency is a major obstacle to the widespread deployment of photocatalysis technology. Many structural engineering strategies have been proposed to address the issue of insufficient activity for semiconductor photocatalysts. Among them, creation of yolk–shell nanostructures which possess many beneficial features, such as large surface area, efficient light harvesting, homogeneous catalytic environment and enhanced molecular diffusion kinetics, has attracted particular attention. This review summarizes the developments that have been made for the preparation and photocatalytic applications of yolk–shell nanostructures. Additional focus is placed on the realization of interfacial charge dynamics and the possibility of achieving spatial separation of charge carriers for this unique nanoarchitecture as charge transfer is the most critical factor determining the overall photocatalytic efficiency. A future perspective that can facilitate the advancement of using yolk–shell nanostructures in sophisticated photocatalytic systems is also presented.